Remifentanil patient-controlled analgesia in labour: six-year audit of outcome data of the RemiPCA SAFE Network (2010–2015). (August 2019) - Melber, A.A.; Jelting, Y.; Huber, M.; Keller, D.; Dullenkopf, A.; Girard, T.; Kranke, P.
Highlights: Analysis of a remifentanil patient-controlled analgesia (PCA) database. RemiPCA SAFE Network has monitored clinical use of remifentanil PCA since 2009. 5740 remifentanil PCA applications at 31 hospitals analysed between 2010 and 2015. No need for maternal ventilation or cardiopulmonary resuscitation was reported. Remifentanil PCA applied within the context of the network is safe and effective. Abstract: Background: The RemiPCA SAFE Network was established to set standards and monitor maternal and neonatal outcomes when using remifentanil for labour analgesia. The aim of this analysis was to describe the development of the network standard and to report maternal and neonatal outcome data, including severe adverse events. Methods: Data sets of the RemiPCA SAFE Network database from the initial six consecutive years (2010–2015) were retrospectively analysed. The data were analysed on an annual basis and set in context with changes of the network standard, i.e. adaptations of the network's standard operating procedure. Main outcomes reported are maternal and neonatal data regarding effectiveness and safety, such as satisfaction, need for bag/mask ventilation and/or cardiopulmonary resuscitation. Results: Among 5740 data sets, no need for maternal ventilation or cardiopulmonary resuscitation was registered. Neonatal cardiopulmonary resuscitations, potentially related to remifentanil, occurred in 0.3%. In parallel with adaptations of the network standard, a moderate rate of maternal hypoxia (oxygen saturation <94% in 24.7%) was found, together with a low rate of supplemental oxygen requirement in neonates (5.0%). Conclusion: The RemiPCA SAFE Network data show that remifentanil patient-controlled analgesia can be applied safely. There is bias when data from real clinical settings are analysed retrospectively. Notwithstanding, the approach taken by the RemiPCA SAFE Network, with constant, systematic and standardised evaluation of multiple parameters during the course of labour, might identify trends and anomalies and guide the development and application of safety standards, when translating knowledge from scientific trials into clinical practice.